Daily field checking list by Walter Rosene, February 26, 1933 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated February 26, 1933. This checklist was used by Walter Rosene to record birds sighted around Beaver Bayou and Rippey Slough with Bob Walker between 9:30 and 12:30. Plustek--flatbed